The battle over private education in Peru 1968-1980: an aspect of the internal debate in the Catholic Church - Klaiber, Jeffrey (1987)
The educational reform (1972) of the Peruvian military under Velasco provoked a major rift within the catholic educational system, which comprised about 8% of the total student population. The hierarchy and progressive groups supported the reform, while middle and upper class catholics opposed it. Since 1963 the government has provided aid to Catholic schools, allowing the church to expand rapidly its educational services in low income areas and in the Andes. But the wealthier Catholic schools resisted the efforts of the government and the church to incorporate them into the same system. By 1975 Catholic education in Peru had split into two systems: one for the rich and one for the middle classes and the poor. Catholic educators also battled over the use of liberation theology textbooks in the classroom and the participation of their teachers in national teachers' strikes. This same polarization has also occurred at the level of the church-affiliated universities.